Why breastfeed?: A literature review (Research, Society and Development, 2021)
The aim of the study was to highlight the benefits of breastfeeding for premature newborns. This is an integrative literature review, using Latin American and Caribbean Literature in Health Sciences, Scientific Electronic Library Online and Medical Literature Analysis and Retrievel System Online, with Health Sciences Descriptors (DECS) “Breastfeeding AND Growth and Development AND Premature”. After applying the inclusion and exclusion criteria, the PRISMA protocol was used to elucidate the selection and a table to highlight the 13 studies chosen to compose the review. Premature infants should receive breast milk as the first and, if possible, the only choice, as this is sufficient for the baby's needs, as well as having several immunological qualities, which will assist in growth, development and immaturity, providing several benefits as well. for mother and child, acting on physical, biological and mental health, but there are difficulties faced in order to enjoy these benefits, as exclusive breastfeeding is not often achieved. It is concluded that breastfeeding must be very well oriented and stimulated for its implementation, as it brings benefits to the mother and the baby, aiding in the well-being and physical and mental health of both.